2015
DOI: 10.1080/09540105.2015.1104653
|View full text |Cite
|
Sign up to set email alerts
|

Honey: an immunomodulatory agent for disorders of the skin

Abstract: Studies have shown that honeys from around the world can inhibit the growth of a range of dermatologically important microbes. As well as reports of the antimicrobial properties of honey, a number of recent in vitro and in vivo studies suggest that honey is able to modulate immunological parameters related to the skin immune system. Paradoxically, both immunestimulatory and anti-inflammatory effects have been observed. In this review, scientific research investigating the immunomodulatory properties of honeys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…We observed that the macrophage spreading index of peritoneal macrophages was increased in mice treated with honey or QU (Table 9) suggesting the immunomodulatory activities of honey and QU. Studies by McLoone, Warnock, & Fyfe (2016) and Abuharfeil, Al-Oran, & Abo-Shehada (1999) also reported immunomodulatory activity of honey. The macrophage spreading index was also increased in animals treated with the mycotoxin, possibly as an indicator of inflammatory reactions.…”
Section: Food and Agricultural Immunologymentioning
confidence: 95%
“…We observed that the macrophage spreading index of peritoneal macrophages was increased in mice treated with honey or QU (Table 9) suggesting the immunomodulatory activities of honey and QU. Studies by McLoone, Warnock, & Fyfe (2016) and Abuharfeil, Al-Oran, & Abo-Shehada (1999) also reported immunomodulatory activity of honey. The macrophage spreading index was also increased in animals treated with the mycotoxin, possibly as an indicator of inflammatory reactions.…”
Section: Food and Agricultural Immunologymentioning
confidence: 95%
“…Among the compounds with biological activity that are present in honey, the compounds that display antioxidant capacity, such as phenolic acids and flavonoids, have received special attention from research groups, due to their role in the prevention of diseases associated with oxidative stress (Álvarez-Suarez et al, 2012;Arunachalam, Parimelazhagan, & Saravanan, 2011). Phenolic compounds are the major functional components of honey and may significantly contribute to its biological activity (Hung et al, 2004;McLoone, Warnock, & Fyfe, 2016). One of the potential benefits of phenolic compounds is to stabilize cell membranes by reducing lipid peroxidation and scavenging free radicals (Chaudhuri, Banerjee, Basu, Sengupta, & Sengupta, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the wound healing capacity of honey is not only through its antiseptic nature, but also through its immunomodulatory effects, which boost the immune system to fight infection (Fig.4.4). The components in honey related to its immunomodulatory properties have not been yet fully identified, but are being attributed to lipopolysaccharide (LPS), a 5.8 kDa component, major royal jelly protein 1, arabinogalactants, polyphenols, and antioxidants (McLoone et al 2016). Different types of honey have been shown to act with different mechanisms, and moreover that some of these mechanisms are more efficient than others (Ranzato et al 2013).…”
Section: Wound Healing Activitymentioning
confidence: 99%